Contents of training work of master's weightlifters of different groups of gravimetric categories - Oleshko V.G; Lutovinov Y.A; Lisenko V.N; Tkachenko K.V (Kharkov National Pedagogical University, 2010)
Maintenance of training work of leading master's weightlifters of Ukraine of different groups of gravimetric categories in preparatory and competition mesocycle. The trainings programs of sportsmen, lead specialists and trainers are analysed. Comparative description of distributing of exercises in grain of work is resulted for sportsmen. Distributing of speed and power exercises for sportsmen in preparatory mesocycle is increased with the increase of groups of gravimetric categories - on 8,2 and 1,4 %.